2017
DOI: 10.18632/oncotarget.17142
|View full text |Cite
|
Sign up to set email alerts
|

WISP-3 inhibition of miR-452 promotes VEGF-A expression in chondrosarcoma cells and induces endothelial progenitor cells angiogenesis

Abstract: Chondrosarcoma is the second most prevalent general primary tumor of bone following osteosarcoma. Chondrosarcoma development may be linked to angiogenesis, which is principally elicited by vascular endothelial growth factor-A (VEGF-A). VEGF-A level has been recognized as a prognostic marker in angiogenesis. WNT1-inducible signaling pathway protein-3 (WISP)-3/CCN6 belongs to the CCN family and is involved in regulating several cellular functions, including cell proliferation, differentiation, and migration. Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…16 MiR-126 is highly induced by long-term laminar shear stress, which subsequently causes the upregulation or downregulation of genes involved in atherosclerosis. [18][19][20] Our previous results indicated that shear stress induces the expression of miR-34a, which promotes endothelial differentiation of EPCs. [18][19][20] Our previous results indicated that shear stress induces the expression of miR-34a, which promotes endothelial differentiation of EPCs.…”
Section: Introductionmentioning
confidence: 95%
“…16 MiR-126 is highly induced by long-term laminar shear stress, which subsequently causes the upregulation or downregulation of genes involved in atherosclerosis. [18][19][20] Our previous results indicated that shear stress induces the expression of miR-34a, which promotes endothelial differentiation of EPCs. [18][19][20] Our previous results indicated that shear stress induces the expression of miR-34a, which promotes endothelial differentiation of EPCs.…”
Section: Introductionmentioning
confidence: 95%
“…41 Highly migratory JJ012(S10) cells were selected in our laboratory, according to our previous methods. 42 , 43 Subpopulations of JJ012 cells were examined by Transwell assay and selected according to their differential invasiveness. After overnight migration, cells that had penetrated through pores and migrated to the underside of filters were trypsinized and harvested for a second round of selection.…”
Section: Methodsmentioning
confidence: 99%
“…In chondrosarcoma, VEGF-A expression was found to correlate with adiponectin expression and tumor stage [182]. In this tumor type, the high expression of WNT1-inducible signaling pathway protein-3 (WISP-3) stimulated angiogenesis by downregulating miR-452 that in turn is able to inhibit the expression of VEGF-A [183].…”
Section: Bone Cancermentioning
confidence: 99%